Analisis Problematika Pembelajaran dan Strategi Penanganannya pada Siswa Kelas IV-B di SD Negeri 101765 Bandar Setia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research addresses learning challenges in Grade IV-B at SD Negeri 101765 Bandar Setia, focusing on limited facilities and parental participation. The study employs a qualitative approach. Interviews with teachers revealed that a shortage of textbooks and physical resources (such as infocus projectors and a library) hindered student motivation. Low parental participation also negatively impacted learning. To overcome these issues, teachers utilized online resources, visual aids, differentiated instruction, personalized approaches, and collaborative learning, while also engaging parents. Learning evaluation encompassed academic results, attitudes, engagement, and teamwork. This research aims to optimize the primary education process.